Living far away from home: The shared stories of the student boarders from a developing country - Malaga, Jose Rabbi B. (Edelweiss Applied Science and Technology, 2025)
Living far away from home can be a unique and transformative experience, but at the same time, it can be a difficult one. This paper depicts the cases and shared stories of four purposively selected student boarders at a state university in Negros. It adopted a narrative inquiry approach and utilized open-ended and discovery-oriented questions for data collection. The rigor of the findings was addressed using member checking, coding, recoding strategies, thick description, data saturation, and data checking. The data explication process applied the six-phase analysis introduced by Braun and Clarke. The themes that emerged from the study formed the elements of a story – Leaving Home for Dreams, The Perks of Living Far Away from Home, A House is Not a Home, and Hanging On. The student boarders left their low-income families in remote towns and cities to pursue their dreams. Living away from home is a big step for students—it's a chance to grow, learn independence, and build lifelong friendships. It also imparts important lessons on sharing and collaboration. On the other side of it, living in a boarding school or dorm isn't always smooth sailing. There's not much privacy, and students often don't have a choice in where or how they live. Living with others isn't always easy—differences can lead to conflicts, and cramped rooms or old facilities only make things harder. Still, many students push through, staying focused on their goals and hoping for better days ahead. Maybe it's time for colleges and local officials to take action and make student housing more comfortable.